Воинство в ямном обществе Северо-Западного Причерноморья - Иванова, С.В.; Цимиданов, В.В. (My University, 2004)
S. Ivanova, V. Tsimidanov. Military in the Pit Society of the Northwest Black Sea Coast In the article the problem of social structure of the inhabitants of the pit community in the territory of the Northwest Black Sea Coast is analyzed. Existence of the specialized group of the military nobility, the usurpers of military function in the society, is one of the major features of the trifunctional structure. Belonging to it was marked in a funeral ceremony by presence of arms units in a tomb. In the analysed 2135 funeral complexes, arms units — arrowheads, flint axes, stone fighting hammers — are found in 24 only that makes up 1,1 % of the sampling. The similar percentage correlation of burial places with weapons is fixed for other regions of the pit community as well. On the Northwest Black Sea Coast only 31,8 % of burial places with arms units are connected with such socially significant feature as increased labour expenses during the burial (creation of a burial mound, additional filling, considerable sizes of a funeral construction). The anthropological data attest presence of weapon in burial places of persons of all age categories. On the whole, the available data testify that in the pit society all capable men were carriers of military function whereas presence of arms units in a tomb can be considered as a sign of certain military merits of the buried person. It does not allow to accept univocally a hypothesis of tFifunctional structure of the pit society and accordingly of existence of the specialized military estate.